NUTRITION FOR CANCER PATIENTS IN DEVELOPING COUNTRIES - Yuni Sufyanti Arief; Siti Nur Qomariah (Lux Mensana: Journal of Scientific Health, 2025)
Introduction. Nutritional problems among cancer patients represent a major clinical and public health challenge because of cancer progression and treatment. In low- and middle-income countries (LMICs), limited healthcare infrastructure, delayed diagnosis, food insecurity, economic hardship, and inadequate nutritional support systems exacerbate the vulnerability of oncology patients. This study aimed to examine current evidence regarding nutritional issues, determinants of malnutrition, nutritional interventions, and barriers to nutritional care among cancer patients in developing countries. Method. This literature review from PubMed and SpringerLink focuses on malnutrition prevalence and oncology nutrition in LMICs. Emphasizing contemporary research from 2015 to 2026, the review includes both pediatric and adult oncology populations. Result&Analysis. The review highlights that malnutrition significantly influences treatment tolerance, quality of life, hospitalization, and survival outcomes. Evidence suggests that early nutritional screening, individualized dietary counseling, oral nutritional supplementation, and multidisciplinary oncology nutrition care can improve patient outcomes. However, implementation in developing countries remains constrained by insufficient resources, a lack of trained professionals, and limited integration of nutrition into oncology services. Discussion. Strengthening nutrition-focused cancer care policies and expanding evidence-based interventions are essential to improving cancer outcomes in resource-limited settings.